2012
DOI: 10.1111/j.1526-4637.2012.01369.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Nonspecific Low-Back Pain in Chinese Adolescents: A Case-Control Study

Abstract: Family history, feeling schoolbag uncomfortable, duration of schoolbag carrying, basketball playing and rest position between classes are the major risk factors for nonspecific LBP in adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 29 publications
2
27
1
2
Order By: Relevance
“…Some studies haven´t found a positive association between LBP and smoking [24,36,37,40]. However, the Feldman et al [10] study found an association between smoking and back pain (OR=2.20; 95% CI: 1.38-3.50), an association also observed in other studies [27, 45,52,53].…”
Section: Modifiable Risk Factorsmentioning
confidence: 35%
See 4 more Smart Citations
“…Some studies haven´t found a positive association between LBP and smoking [24,36,37,40]. However, the Feldman et al [10] study found an association between smoking and back pain (OR=2.20; 95% CI: 1.38-3.50), an association also observed in other studies [27, 45,52,53].…”
Section: Modifiable Risk Factorsmentioning
confidence: 35%
“…The investigation by Yao et al [36] included 1,214 Chinese adolescents, and the results revealed that family history was related to the presence of LBP (OR=2.57, 95% CI: 1.85-3.58), however the Kovacs et al [37] study, performed in adolescents living in the island of Majorca (Spain), didn´t verify this relationship.…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 86%
See 3 more Smart Citations